2019
DOI: 10.1038/s41467-019-09046-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils promote the development of reparative macrophages mediated by ROS to orchestrate liver repair

Abstract: Phagocytes, including neutrophils and macrophages, have been suggested to function in a cooperative way in the initial phase of inflammatory responses, but their interaction and integration in the resolution of inflammation and tissue repair remain unclear. Here we show that neutrophils have crucial functions in liver repair by promoting the phenotypic conversion of pro-inflammatory Ly6C hi CX 3 CR1 lo monocytes/macrophages to pro-resolving L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(242 citation statements)
references
References 70 publications
8
196
0
2
Order By: Relevance
“…Importantly whilst numerous studies have shown that APAP induced liver damage is not driven by neutrophils 55,56 , it is clear that neutrophil activation and hepatic infiltration occurs after APAP induced liver damage 16,57,58 . This neutrophil infiltration is increasingly thought to represent the innate immune reparative response designed to aid a return to hepatic homoeostasis after acute injury 15,59,60 . Our data demonstrate that platelet CLEC-2 deficiency enhances both hepatic neutrophil infiltration and neutrophil phagocytic function.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly whilst numerous studies have shown that APAP induced liver damage is not driven by neutrophils 55,56 , it is clear that neutrophil activation and hepatic infiltration occurs after APAP induced liver damage 16,57,58 . This neutrophil infiltration is increasingly thought to represent the innate immune reparative response designed to aid a return to hepatic homoeostasis after acute injury 15,59,60 . Our data demonstrate that platelet CLEC-2 deficiency enhances both hepatic neutrophil infiltration and neutrophil phagocytic function.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, recent reports have demonstrated that NO, in association with other ROS, is critically involved in neutrophil extracellular trap (NET) formation [30]. Curiously, it was also recently reported that neutrophils might participate in the resolution of inflammation mediated by reparative macrophages [5]. It has been well established that LPS and inflammatory cytokines stimulate NO production by inducing iNOS expression [31].…”
Section: Discussionmentioning
confidence: 99%
“…LPS signaling through TLR 4 induces macrophage activation by regulating intracellular pathways involved in cytokine, lipid mediator and oxygen reactive species (ROS) production, in a process regulated by calcium signaling [2,3]. The mediators released by activated macrophages play critical roles in neutrophil recruitment and activation, and therefore, influence the progress of immune responses as well as the development of many inflammatory diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism may not only apply to enhancing the antimicrobial response. For example, it has also been implicated in the stimulation of wound healing through enhancing the differentiation of pro-resolution macrophages in the liver [61].…”
Section: Bacterial Infectionsmentioning
confidence: 99%